2022
DOI: 10.3389/fonc.2022.968547
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the glutathione S-transferase Mu (GSTM) gene family in ovarian cancer identifies prognostic and expression significance

Abstract: BackgroundOvarian cancer (OC) is one of the most common types of gynecologic tumor over the world. The Glutathione S-transferase Mu (GSTM) has five members, including GSTM1-5. These GSTMs is involved in cell metabolism and detoxification, but their role in OC remains unknown.MethodsData from multiple public databases associated with OC and GSTMs were collected. Expression, prognosis, function enrichment, immune infiltration, stemness index, and drug sensitivity analysis was utilized to identify the roles of GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…[21] Similarly, a large number of studies have found that GSTM3 plays an important role in glioma, pancreatic cancer, and esophageal cancer. [22][23][24][25] This also con rms the value of this study. HPGD undertakes a wide range of functions in the body, and the proteins it encodes are distributed throughout the body.…”
Section: Discussionsupporting
confidence: 85%
“…[21] Similarly, a large number of studies have found that GSTM3 plays an important role in glioma, pancreatic cancer, and esophageal cancer. [22][23][24][25] This also con rms the value of this study. HPGD undertakes a wide range of functions in the body, and the proteins it encodes are distributed throughout the body.…”
Section: Discussionsupporting
confidence: 85%
“…Database analysis of ovarian cancer cells identified that the high expression of GSTM2, -3, and -4 correlates with the decreased expression of immune checkpoint molecules, such as CTLA-4 and TIGIT. Thus, the results highlighted the expression of GSTM2, -3, and -4 in promoting immune escape in ovarian cancer [62]. In addition, GSTA3 was identified as one of the highest contributing GST is a family of phase II detoxification enzymes that protect cells from the attack of reactive electrophiles.…”
Section: Antioxidant Metabolism Associated With Cancer Cell Immune Es...mentioning
confidence: 88%
“…Moreover, there is a report that the high expression of GPx3 in alveolar type 2 (AT2) epithelial cells induced the production of IL-10 in the premetastatic niche. IL-10-producing GPx3 AT2 cells were found to increase Treg and decrease CD4+ T cell proliferation; conversely, the deletion of GPx3 in AT2 cells suppressed lung metastasis [62]. GPx is a selenium-containing antioxidant enzyme that protects cells by reducing hydrogen peroxide and lipid peroxide into water and lipid alcohols.…”
Section: Antioxidant Metabolism Associated With Cancer Cell Immune Es...mentioning
confidence: 99%
“…Besides, a phase I study published in 2011 investigated that PHA-793887 induces severe, dose-related hepatic toxicity [ 57 ]. However, some latest studies have revealed the effective role of PHA-793887 in against osteosarcoma [ 58 ], lung cancer [ 59 ], prostate cancer [ 60 ] and ovarian cancer [ 61 ]. Therefore, our findings provided new application of PHA-793887 in HCC and theoretical basis for promoting the clinical application of PHA-793887 in CTNNB1-mutant HCC.…”
Section: Discussionmentioning
confidence: 99%